Konstruksi Wacana Ketakutan Kolektif dalam Adegan Trinity Test Film Oppenheimer 2023 - Yurfina Martha Kusuma Dewi; Hilda Rahmah (CV. ITTC INDONESIA, 2026)
This study is based on the problem that the representation of the Trinity Test in the film Oppenheimer (2023) not only reconstructs historical events but also constructs a discourse of collective fear toward global nuclear threats, which has not been extensively examined in film studies, particularly in relation to dynamic and historical scenes involving geopolitical and humanitarian trauma. This study aims to analyze the construction of collective fear discourse in the Trinity Test scene of the film Oppenheimer (2023). This research employs a descriptive qualitative approach using Gillian Rose’s visual discourse analysis method, which consists of three sites of analysis: the site of the image, the site of production, and the site of the audience. The data were collected through visual documentation, intensive observation, dialogue transcription, and coding of visual and audio elements in the Trinity Test scene. The data were analyzed interpretatively based on visual elements, cinematic strategies, and audience reception. The findings show that collective fear in the film Oppenheimer (2023) emerges as a shared anxiety regarding the potential for global destruction caused by the destructive power of nuclear technology. This fear is not only represented as the individual emotions of scientists but also as a form of humanitarian trauma reflecting the relationship between science, state power, and the threat of nuclear warfare that may endanger human civilization.